2003
DOI: 10.1002/hlca.200390349
|View full text |Cite
|
Sign up to set email alerts
|

Pentopyranosyl Oligonucleotide Systems. 9th Communication

Abstract: Dulio Arigoni zu seinem 75. Geburtstag gewidmet, in Erinnerung an gute alte Zeiten Pyranosyl-RNA (−p-RNA× ) is an oligonucleotide system isomeric to natural RNA and composed of the very same building blocks as RNA. Its generational, chemical, and informational properties are deemed to be those of an alternative nucleic acid system that could have been a candidate in Nature×s evolutionary choice of the molecular basis of genetic function. We consider the study of the chemistry of p-RNA as etiologically relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
13

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 99 publications
(89 reference statements)
0
50
0
13
Order By: Relevance
“…[133,134,141] Wie bei der homo-DNA ist die Duplexierung durch Watson-Crick-Paarung in antiparalleler Strangorientierung gegenüber Paarung in paralleler Orientierung viel stärker bevorzugt als bei der DNA: [99,141] Für ein Adenin-und Thymin-haltiges Hexadecamer der p-RNAReihe, dessen Duplex mit dem antiparallel-komplementären Strang unter Standardbedingungen über 60 8C schmilzt, wurde keinerlei Duplexierung mit seinem parallel-komplementären Strang beobachtet. [141] Dies entspricht der Erwartung, dass Oligomersysteme mit starker Rückgratneigung aus geometrischen Gründen [99] keine [41][42][43]. [137,139,140] Gleiches gilt für die Erwartung, wonach sogenannte "dangling bases" einen p-RNA-Duplex nur dann stabilisieren, wenn sie am 2'-Ende eines Stranges sitzen, und dass sie dies als Purine stärker tun, als in Form von Pyrimidinen (Abbildung 43 und 44).…”
Section: Hexopyranose-nukleinsäurenunclassified
See 1 more Smart Citation
“…[133,134,141] Wie bei der homo-DNA ist die Duplexierung durch Watson-Crick-Paarung in antiparalleler Strangorientierung gegenüber Paarung in paralleler Orientierung viel stärker bevorzugt als bei der DNA: [99,141] Für ein Adenin-und Thymin-haltiges Hexadecamer der p-RNAReihe, dessen Duplex mit dem antiparallel-komplementären Strang unter Standardbedingungen über 60 8C schmilzt, wurde keinerlei Duplexierung mit seinem parallel-komplementären Strang beobachtet. [141] Dies entspricht der Erwartung, dass Oligomersysteme mit starker Rückgratneigung aus geometrischen Gründen [99] keine [41][42][43]. [137,139,140] Gleiches gilt für die Erwartung, wonach sogenannte "dangling bases" einen p-RNA-Duplex nur dann stabilisieren, wenn sie am 2'-Ende eines Stranges sitzen, und dass sie dies als Purine stärker tun, als in Form von Pyrimidinen (Abbildung 43 und 44).…”
Section: Hexopyranose-nukleinsäurenunclassified
“…Einfluss überhängender Basen auf die Stabilität von p-RNA-Haarnadel-Komplexen. [140,141] A. Eschenmoser…”
Section: Angewandte Chemieunclassified
“…Consequently, it is not possible to form chimeric double helices between a strand of homo-DNA and a strand of RNA. The discovery of a structurally regular isomer of RNA, pyranosyl RNA, or pRNA (Figure 9c still possible to form a double-stranded, base-paired double helix (Pitsch et al, 2003). Again, the structure of the helix is incompatible with that of RNA.…”
Section: Rna Latermentioning
confidence: 99%
“…One study revealed limitations of the conformational diversity of canonical nucleic acids by systematically synthesizing alternative nucleic acid structures. Markedly lower level of helicity was exhibited by pentopyranosyl nucleic acids in comparison to ribonucleic acid, lending support to the idea that the pentofuranose structure is responsible for the helical shape of the duplex in RNA and ▶ DNA (Eschenmoser and Dobler 1992;Pitsch et al 2003). Another study explored the assemblage and accumulation of pentofuranoses through a borate-mediated stabilization of cis-diols in furanose form (Prieur 2001;).…”
Section: Fragmentation Of Interstellar Cloudsmentioning
confidence: 87%